Assessing algal reef (coralligenous) distribution and volume using geomoprphometry (Apulian shelf, Italy) - Marchese, F; Bracchi, VA; Basso, D; Savini, A (Università di Roma La Sapienza, 2019)
Algal reefs (=Coralligenous) has been reported as one of the most relevant habitat along the Apulian continental shelf (Southern Italy). They represent one of the most important hotspot of biodiversity in the Mediterranean Sea, actually included in the list of endangered habitats by governmental organizations and conservation agencies. Due to its carbonate framework, made primarily by the concretion of crustose coralline algae, it is sensitive to the ongoing global change that can produces a negative impact on the calcification of the organisms’ skeleton. In this way, geomorphometric techniques may be applied to produce quantitative data in term of area and volume of biogenic carbonate developed by such bioconstructions, and this represents a fundamental topic in a scenario of ocean acidification and global warming. This study, combining acoustic survey techniques and geomorphometric analysis, developed a new experimental methodology allowing to successfully supporting a preliminary quantitative assessment of algal reef distribution and volume along the Apulian shelf. Within the framework of the BIOMaP Project (P.O. FESR 2007/2013), high resolution multibeam data, using the Teledyne RESON SeaBat 8125 and 8160, were acquired in order to locate Coralligenous along the Apulian continental shelf from 10 down to 100 m of water depth. Coralligenous has been mapped as unique biocoenosis or mosaicking other substrates. Firstly we selected three small Digital Terrain Models (DTMs) with resolution of 0.3 and 2 m corresponding to area where testing the methodology. The first step was to detect all the Coralligenous build-ups distributed on the mapped seafloor usable for geomorphometric analysis of the DTMs. Due to the rising of build-ups from the seafloor, we cut coralligenous reliefs. The Topographic Position Index tool of the SAGA software (System for System for Automated Geoscientific Analyses), was then used to support the performed analysis. A flat reference surface was produced for volume calculation by using the ...